PENGARUH CORPORATE GOVERNANCE, KUALITAS AUDIT DAN PERGANTIAN AUDITOR TERHADAP KONSERVATISME (Studi Empiris âMost Trusted Company Based On Corporate Governance Perception Indexâ di BEI Tahun 2007-2010) - Anindhita Ismawardani, 08.05.52.0085; Nuswandari, Cahyani (Students Journal of Accounting and Banking, 2013)
This studys aim is to examine and analyze the effect of corporate governance, audit quality and auditor turnover for the integrity of the financial statements in the "Most Trusted Company Based On Corporate Governance Perception Index" in Indonesia. The integrity of the financial statements is defined as the extent to which the financial statements show a true and fair information. Population taken in this study is a company registered in the selection of "Most Trusted Company Based On Corporate Governance Perception Index" listed on the Indonesia Stock Exchange in 2007-2010. Samples were taken by using purposive sampling, the samples are selected on the basis of compliance with the criteria specified characteristics. Based on the criteria obtained a sample of 52 companies. To test the hypothesis which is proposed in this study ,the data were analyzed using multiple linear regression. The results showed that the variables of corporate governance, audit quality and auditor turnover has no effect on the integrity of the financial statements.Keywords: Corporate Governance, Audit quality, Auditor turnover, Accounting conservatism